1997
DOI: 10.1046/j.1365-2648.1997.1997025144.x
|View full text |Cite
|
Sign up to set email alerts
|

A Critical review of the literature on sharps injuries: epidemiology, management of exposures and prevention

Abstract: This article reviews the literature related to the epidemiology, prevention and management of sharps injuries in health care workers, particularly nurses, and the subsequent risk of harm. The studies are reviewed chronologically, beginning with the efforts to reduce sharps injuries by changing behaviours, followed by the introduction of barriers to protect the caregiver, and finally, the engineering of safer products. Initial efforts to prevent sharps injuries focused on placing rigid, disposal containers at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 95 publications
1
48
0
2
Order By: Relevance
“…Unvaccinated individuals may have a 6-30% risk of becoming infected with the virus following an injury. 40 A study from the UK quoted the risk associated with transmission of HBV to a non-immune health care worker to range from 2% if the source patient is Hepatitis Be antigen negative to 40% if the patient is Hepatitis Be antigen positive. 41 Prospective studies of health care workers exposed to HCV through a needlestick or other NSIs have found that the incidence of anti-HCV sero-conversion averages 1.8% (range 0%-7%) per injury.…”
Section: Discussionmentioning
confidence: 99%
“…Unvaccinated individuals may have a 6-30% risk of becoming infected with the virus following an injury. 40 A study from the UK quoted the risk associated with transmission of HBV to a non-immune health care worker to range from 2% if the source patient is Hepatitis Be antigen negative to 40% if the patient is Hepatitis Be antigen positive. 41 Prospective studies of health care workers exposed to HCV through a needlestick or other NSIs have found that the incidence of anti-HCV sero-conversion averages 1.8% (range 0%-7%) per injury.…”
Section: Discussionmentioning
confidence: 99%
“…In the US, 800,000 of the approximately 5.6 million health care workers suffer needle stick injuries each year. 12 Data from the EPINet system suggest that at an average hospital, workers incur approximately 30 needle-stick injuries per 100 beds per year. 13 About 80% of HCV-positive surgical operation room personnel in a hospital in Pakistan had more than four needle stick injuries per year in five years.…”
Section: Discussionmentioning
confidence: 99%
“…Os acidentes com agulhas são os principais responsáveis por expor os profissionais de saúde ao risco de adquirir infecções graves, como a AIDS e as hepatites estudos (10)(11) . A primeira implica substituir os materiais potencialmente perfurantes por aqueles com design seguro.…”
Section: Discussão E Conclusõesunclassified